دلالة (أحد) في (قل هو الله أحد) عند أصحاب المتشابهات اللفظية - مايل محمد عبد ذياب (Al-Adab Journal, 2019)
This book deals with the verses of the Holy Quran to highlight the rhetorical aspects and the miraculous secrets, especially the issues of Qur’anic interpretation. They guide the verses with great rhetorical guidance, and depend on the language of their language and so on. Important books in the field of interpretation of the Koran, and one of the striking issues modern owners of verbal similarities of the meaning of the word (one) in the Surah Al-Ikhlas (Say God is one) especially Granati, and something goes on Ansari, a question of unification and missed the speech in about seven full pages When the Granati in his book the angel of interpretation